2007
DOI: 10.1094/fg-2007-0918-02-rs
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Studies on the Dry Matter Production and Quality of Annual and Perennial Grasses

Abstract: A field experiment for determining dry matter and quality of annual and perennial grasses was conducted during 2005 and 2006 at Cattle Research Station, Manasbal on a silty clay loam soil that was low in available nitrogen, medium in available phosphorus and potassium, with neutral pH. The treatments consisted of one annual grass (Oat, Avena sativa L.) and four perennial grasses (orchardgrass, Dactylis glomerata L.; perennial ryegrass, Lolium perenneL.; tall fescue, Festuca arundinacea L.; and hybrid Phalaris,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The average dry matter yield of both native and exotic grasses varies considerably from 2.5 t/ha in Agrostis spp. to 10.0 t/ha in Dactylis glomerata in Kashmir Himalaya (Dar et al, 2007) [19] . However, it was found that N @ 240-360 kg/ha fertilized cocksfoot could be harvested four times per vegetation season.…”
Section: Fodder Yieldmentioning
confidence: 99%
“…The average dry matter yield of both native and exotic grasses varies considerably from 2.5 t/ha in Agrostis spp. to 10.0 t/ha in Dactylis glomerata in Kashmir Himalaya (Dar et al, 2007) [19] . However, it was found that N @ 240-360 kg/ha fertilized cocksfoot could be harvested four times per vegetation season.…”
Section: Fodder Yieldmentioning
confidence: 99%
“…There are no satisfactory facilities available in the far off villages let alone high altitude pastures. [34]. The grasses, legumes and tree species best suited to the location need to be identified and incorporated.…”
Section: Shrinkage Of Village Pastures Previouslymentioning
confidence: 99%